PEDAGOGICAL STRATEGIES THAT IMPROVE CHILDREN’S PLAY-BASED LEARNING - Monkevičienė, Ona; Stankevičienė, Kristina; Autukevičienė, Birutė; Jonilienė, Marija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This article focuses on the analysis of the issue of children and play-based learning. The theoretical position that play and learning are frequently integrated processes for a child and that there are methods of teacher-child interaction which make play-based learning more efficient, is followed. The pedagogical strategies that enable a child to learn through play without disrupting the authenticity of the play itself are theoretically substantiated: the strategy for promotion of children’s learning “en passant”, the strategy for initiation and promotion of joint attention, the strategy for promotion of children’s learning from peers, the strategy for promotion of communicative teacher-children encounters in play and the strategy for promotion of children’s reflection on play-based learning. On the basis of the qualitative research, the specific methods of practical implementation of each strategy have been described.